GENDER DIFFERENCE OF ELEMENTARY LEVEL L2 LEARNERS - Gharizi Matiini (LITERA, 2019)
The study aims to seek the difference of language abilities between male and female young learners. The previous studies have already given plenty of proofs that there are some boundaries between male and female Language learners in achieving language ability. However, there are only few studies looking for gender difference of language ability in younger L2 learners. The present study used two young learners as the participants and the data is collected only in spoken language. Therefore, the data analysis only focused on the verbal ability and the use of linguistic device. The study found that male learner was more fluent in speaking L2 than the female one. He produced more words and used more in sentence conjunction than the female learner did. He also talked smother and more detail than the female leaner. However, both learners were equal in using intensifier. To be concluded, though many studies stated that female learners master L2 quicker than male learner, it might be different when it comes to the younger level L2 learners. Here, both male and female learners had balance level of ability of L2 learning.Keywords: gender difference, young L2 learner, language ability